Monitoring age‐related trends in genomic diversity of Australian lungfish. Issue 16 (27th July 2018) - Schmidt, Daniel J.; Fallon, Stewart; Roberts, David T.; Espinoza, Thomas; McDougall, Andrew; Brooks, Steven G.; Kind, Peter K.; Bond, Nick R.; Kennard, Mark J.; Hughes, Jane M.
Abstract: An important challenge for conservation science is to detect declines in intraspecific diversity so that management action can be guided towards populations or species at risk. The lifespan of Australian lungfish ( Neoceratodus forsteri ) exceeds 80 years, and human impacts on breeding habitat over the last half century may have impeded recruitment, leaving populations dominated by old postreproductive individuals, potentially resulting in a small and declining breeding population. Here, we conduct a "single‐sample" evaluation of genetic erosion within contemporary populations of the Australian lungfish. Genetic erosion is a temporal decline in intraspecific diversity due to factors such as reduced population size and inbreeding. We examined whether young individuals showed signs of reduced genetic diversity and/or inbreeding using a novel bomb radiocarbon dating method to age lungfish nonlethally, based on 14 C ratios of scales. A total of 15, 201 single nucleotide polymorphic (SNP) loci were genotyped in 92 individuals ranging in age from 2 to 77 years old. Standardized individual heterozygosity and individual inbreeding coefficients varied widely within and between riverine populations, but neither was associated with age, so perceived problems with recruitment have not translated into genetic erosion that could be considered a proximate threat to lungfish populations. Conservation concern has surrounded Australian lungfish for over a century. However, our results suggest that long‐lived threatened species can maintain stable levels of intraspecific variability when sufficient reproductive opportunities exist over the course of a long lifespan.